Can the marketization of urban land transfer improve energy efficiency?. (1st March 2023) - Yang, Yanjun; Xue, Rui; Zhang, Xiaoxi; Cheng, Yutai; Shan, Yuli
Abstract: Local government intervention in land resource allocation can lead to the misallocation of land resources and serious pollutant emissions. As an important market-oriented economic reform in China, the marketization of urban land transfer (MULT) might have the potential to contribute to improving resource allocation efficiency by curbing local government intervention. Therefore, this study aims to provide empirical evidence on the impact of MULT on energy efficiency. We improve the MULT evaluation method to test the mechanism through which MULT affects energy efficiency. The results show that, first, the proportion of land sold by allocation and listing methods, which is characterized by a low degree of marketization, has rapidly increased in recent years, lowering the overall level of MULT. Second, MULT has a direct and significant positive impact on improving energy efficiency. Third, the mechanism analysis indicates that MULT helps enhance energy efficiency by advancing industrial structure optimization and technological progress. Moreover, the heterogeneity analysis demonstrates that the impact of MULT on improving energy efficiency differs significantly in different reform stages and between central and peripheral cities. This study sheds light on the importance of land resource allocation in improving energy efficiency and thus has practical policy implications for promoting low-carbon energy transition in emerging countries. Highlights: The impact of MULT on energy efficiency is empirically investigated. Overall, the MULT reform has not improved the marketization level of land transfer. The screening effect of MULT has a direct positive effect on energy efficiency. Industrial structure optimization and technological progress are mechanisms. The impact of MULT on energy efficiency differs in reform stages and cities.